Substituted phenothiazines: synthesis and in silico evaluation of D4 dopamine receptor inhibition - Kumar S.; Kumar G.; Shukla I.C. (My University, 2025)
In the present paper we describe synthesis and molecular docking simulation of substituted phenothiazines. Halonitrobenzenes on reaction with thiols give 2-amino-2′-nitrodiphenylsulphides which on formylation with 90% formic acid yield 2-formamido-2′-nitrodiphenyl sulfides. This compound undergoes Smiles rearrangement to provide phenothiazines. To evaluate the antipsychotic property of the synthesized phenothiazines derivatives (5a–d and 7), molecular docking simulation study were performed into the binding pocket of D4 dopamine receptor. These compounds have shown acceptable binding affinity with the binding pocket of the D4 dopamine receptor similar to known inhibitors. Whereas, compound 7 has displayed higher affinity for D4 dopamine receptor compared to D3 and D2 receptors. All compounds interacted with critical residues for the inhibition of D4 dopamine receptor and hence can be developed as potent antipsychotic drugs. © 2020, Springer Nature Switzerland AG.